Physical and Flavor Profiles of Arabica Coffee as Affected by Cherry Storage Before Pulping - Yusianto .; Dwi Nugroho (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2014)
Harvesting and pulping process of coffee cherry in the same day is inaccesible. Storage of coffee cherry before pulping was carried out incorrectly. Some storage treatments before pulping of Arabica coffee cherry had been examined at Indonesian Coffee and Cocoa Research Institute using Arabica coffee cherries from Andungsari Experimental Garden, Bondowoso, East Java. Treatments of the experiment were method and period of cherry storage. Methods of coffee cherry storage were put in plastic sacks; immerse in water, without water replacement; and immerse in water with daily water replacement. Period of coffee cherry storage were 0, 1, 2, 3, 4, 5, 6, and 7 days. After storage treatments, the coffee cherries were pulped, fermented, washed, sundried, and dehulled. The experiment were carried out using randomized block design with three replications. Observation of coffee cherry during storage periods was done on the physical and temperature. Observation of the green coffee were done on the color dan bulk density. The green coffee were roasted at medium roast level for sensory analysis. Observation of roasting profile were out-turn, bulk density and pH of roasted coffee. Sensory analysis used Specialty Coffee Association of America method. Methods and period of cherry storage before pulping significanly influence on the cherry color, parchment color, green coffee color, and the flavor profile of Arabica coffee. Color of dry parchment changed to be red-brown becouse of cherry immersed in water for two days or more. In plastic sacks, Arabica coffee cherry may be stored only for two days, but underwater with or without water replacement, should be not more than five days. Green and sensory quality of Arabica coffee will be deteriorated after five days storage underwater. Coffee cherry storage immerse in water with daily replacing water may improve sensory quality of Arabica coffee.Key word: Arabica coffe, storage, pulping, flavor, physical perqutions